A new method for insertion of long intestinal tube for small bowel obstruction: Nonendoscopic over-the-wire method via short nasogastric tube. Issue 47 (November 2016) - Sekiba, Kazuma; Ohmae, Tomoya; Odawara, Nariaki; Moriyama, Makoto; Kanai, Sachiko; Tsuboi, Mayo; Saito, Tomotaka; Uchino, Koji; Akamatsu, Masatoshi; Okamoto, Makoto
Abstract : Abstract: It is often difficult to insert a long intestinal tube (LT) in patients with small bowel obstruction (SBO). We developed a novel technique for inserting an LT without endoscopy called nonendoscopic over-the-wire method via short nasogastric tube (NEWSt). We evaluated the efficacy and safety of NEWSt. We performed a retrospective study of patients who underwent LT insertion for SBO without any indications of strangulation with either NEWSt (n = 16) or endoscopy (n = 17) between November 2011 and February 2015 at our hospital. Univariate analysis was used to assess the success rate of LT placement beyond the duodenojejunal flexure, time required for the procedure, clinical outcomes, and adverse events. The success rate was 100% in both groups. Procedure time was numerically, but not statistically, shorter in the NEWSt group compared with the endoscopy group (24 ± 13 vs 30 ± 13 min; P = 0.174). There were no statistically significant differences between the 2 groups in terms of surgery rate (31% vs 12%; P = 0.225), fasting period (11.3 ± 6.3 vs 9.9 ± 4.5 days; P = 0.482), hospital stay (26.4 ± 22.1 vs 18.7 ± 7.0 days; P = 0.194), and recurrence rate (19% vs 24%; P = 1.0). No serious adverse event was observed in the NEWSt group, whereas serious aspiration pneumonia was observed in 2 patients after LT insertion in the endoscopy group. Without endoscopy, NEWSt enabled the high success rate and the short procedure time for the LT insertion. Prospective, randomized controlled trials are needed.